Resistance to ‘Candidatus Liberibacter asiaticus,’ the Huanglongbing Associated Bacterium, in Sexually and/or Graft-Compatible Citrus Relatives - Alves, Mônica N.; Lopes, Silvio A.; Raiol-Junior, Laudecir L.; Wulff, Nelson A.; Girardi, Eduardo A.; Ollitrault, Patrick; Peña, Leandro (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is the most destructive, yet incurable disease of citrus. Finding sources of genetic resistance to HLB-associated ‘Candidatus Liberibacter asiaticus’ (Las) becomes strategic to warrant crop sustainability, but no resistant Citrus genotypes exist. Some Citrus relatives of the family Rutaceae, subfamily Aurantioideae, were described as full-resistant to Las, but they are phylogenetically far, thus incompatible with Citrus. Partial resistance was indicated for certain cross-compatible types. Moreover, other genotypes from subtribe Citrinae, sexually-incompatible but graft-compatible with Citrus, may provide new rootstocks able to restrict bacterial titer in the canopy. Use of seedlings from monoembryonic species and inconsistencies in previous reports likely due to Las recalcitrance encouraged us to evaluate more accurately these Citrus relatives. We tested for Las resistance a diverse collection of graft-compatible Citrinae species using an aggressive and consistent challenge-inoculation and evaluation procedure. Most Citrinae species examined were either susceptible or partial resistant to Las. However, Eremocitrus glauca and Papua/New Guinea Microcitrus species as well as their hybrids and those with Citrus arose here for the first time as full-resistant, opening the way for using these underutilized genotypes as Las resistance sources in breeding programs or attempting using them directly as possible new Las-resistant Citrus rootstocks or interstocks.